Binder jetting additive manufacturing: Three-dimensional simulation of micro-meter droplet impact and penetration into powder bed. (February 2022) - Deng, Hongxin; Huang, Yanlu; Wu, Shibiao; Yang, Yongqiang
Abstract: In binder jetting additive manufacturing, the process of the micro-meter droplet impact and penetration into the powder bed, which is mostly dependent on the capillary dynamics, dominates the lateral spreading and vertical penetrating and even the dimensional accuracy. In this paper, capillary flow in tubes of different sizes were researched in advance to obtain the basic understanding of liquid flow in porous material. Then, the simulations of single micro-meter droplet impacting and penetrating into the powder bed were undertaken to find out the effects of particle size and contact angle on the binder flow within the powder bed. The results suggest that smaller powder particle size does not always improve the accuracy, and excessive wettability may lead to gas bubble entrapped and thus lower density and accuracy of green part. A new commentate was proposed to explain the regime of the binder droplet interacting with the powder bed, of which the binder penetration process being divided into the impact-driving stage and the capillary-driving one. The numerical results coincide well with the experimental ones.